2017
DOI: 10.3389/fpsyg.2017.01448
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Parents' Preferences and Parents' Perceptions of Child Preferences of Picturebooks

Abstract: This study examined factors influencing parents' preferences and their perceptions of their children's preferences for picturebooks. First, a content analysis was conducted on a set of picturebooks (N = 87) drawn from the sample described in Wagner (2013); Then, parents (N = 149) rated the books and several content properties were examined for their ability to predict parents' preferences and their perception of their children's preferences. The initial content analysis found correlated clusters of disparate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(50 reference statements)
4
15
0
1
Order By: Relevance
“…Our findings suggest that books vary appreciably along the dimension of gender in terms of both their content and characters. The gender distribution of characters we observe is comparable to that reported previously in a smaller sample of books (Wagner, 2017).…”
Section: Methods and Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings suggest that books vary appreciably along the dimension of gender in terms of both their content and characters. The gender distribution of characters we observe is comparable to that reported previously in a smaller sample of books (Wagner, 2017).…”
Section: Methods and Resultssupporting
confidence: 88%
“…The main character(s) were classified as either female, male, mixed, or indeterminate (Wagner, 2017). If there was more than one primary character, and their gender composition was heterogeneous, that group was classified as mixed.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Yet including informational books in home settings may be challenging as a number of studies revealed that there is a perception among children and adults that boys prefer informational books (Chapman et al, ; Wagner, ). Because parents try to select books that interest their children (Tekin & Tekin, ), if they perceive informational books as being something their boys will like, they are more likely to expose them to this type of book.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that parents are generally the ones who purchase books for their children or select books to borrow from the library, a surprisingly small number of studies have examined parents' genre preferences when making these selections (Wagner, ). Although Anderson et al () found that parents selected informational books nearly as often as narratives, in the few other studies that we found, parents reported a clear preference for storybooks over other genres (Robertson & Reese, ; Saracho & Spodek, ).…”
Section: Narrative and Informational Genresmentioning
confidence: 99%
See 1 more Smart Citation